90 DOES LACK OF MEDICAL INSURANCE AFFECT HEALTH CARE UTILIZATION AND HEALTH OUTCOMES IN NONELDERLY ADULTS? A SYSTEMATIC REVIEW OF STUDIES CONDUCTED IN THE UNITED STATES. Issue 1 (1st January 2007) - Freeman, J. D.; Martin, D.
Abstract : Purpose: To evaluate the evidence that lack of medical insurance has a significant causal effect on health care utilization and health outcomes of nonelderly adults in the United States. Method: A systematic search of the on-line literature database PubMed MEDLINE using MeSH terms, key words, and Related Articles search algorithms was performed between November 2005 and March 2006. Results were primarily excluded by screening study titles and identifying unrelated topics. In the secondary screening, an abstract of each article was examined for the inclusion criteria. To be included in this review studies had to be published after 1991; study a population of adults between 18 and 64 years; and include analyses that specifically compared an uninsured group with an appropriate control group. Longitudinal cohort studies needed to follow patients for a minimum of 2 years. Quasiexperimental studies were excluded if multiple exogenous policy events occurred during the study period. Mortality analyses that did not measure disease-specific mortality as a health outcome were excluded. Results: A total of 7, 582 studies, including numerous duplicates, were primarily screened. One hundred seventy studies passed the primary and secondary screenings and were analyzed in detail. Ten studies fulfilled the criteria to be included in this review: two longitudinal cohort studies employing standard regression analysis (Baker, Sudano, et al, 2001, and Sudano and Baker, 2003), three longitudinal cohort studies employing instrumental regression analysis (Bhattacharya, Goldman, et al, 2003; Johnson and Crystal, 2000; and Meer and Rosen, 2004), three quasiexperimental studies (Bograd, Ritzwoller, et al, 1997; Kwack, Sklar, et al, 2004; and Steiner, Price, et al, 2002), and two nontraditional quasiexperimental studies (Doyle, 2003, and Perry and Rosen, 2001). Conclusion: It is apparent that a general negative association between lack of medical insurance, utilization of care, and health outcomes exists as evidenced by several large critical reviews. However, with the debate on the validity of causal inferences on standard and instrumental variable regression analyses of longitudinal cohort data and the mixed results of quasiexperimental studies, there is only weak evidence found in a systematic review of the literature to confirm the widely held belief of a positive causal effect of health insurance on medical care utilization or health outcomes in nonelderly adults in the United States.